2016
DOI: 10.1007/s00005-016-0421-y
|View full text |Cite
|
Sign up to set email alerts
|

Activated and Memory T Lymphocytes in Children with Gaucher Disease

Abstract: Gaucher disease (GD) is the most prevalent lysosomal storage disorder. Gaucher disease is associated with remarkable alterations in the immune system, and GD patients are more susceptible to infections and are at a higher risk of developing autoimmune disorders and malignancies. In a case-control study, we used three-color flow cytometric immunophenotyping for determination of the frequency of lymphocyte subpopulations and activated T lymphocytes among 18 children with GD1 under enzyme replacement therapy mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Also, Zahran and colleagues used three-color flow cytometric immunophenotyping for determination of the frequency of lymphocyte subpopulations and activated T lymphocytes in the peripheral blood among eighteen children with Gaucher disease type 1. They showed increases in the frequencies of activated T lymphocytes (CD3+HLA-DR+ ), activated T-helper cells (CD4+HLA-DR+) and activated T-suppressor/cytotoxic cells (CD8+HLA-DR+) in Gaucher disease type 1 as compared to healthy children [110]. Shoenfeld and coworkers demonstrated a significant increase in the incidence of autoantibodies against 14 autoantigens in the sera of 43 patients with Gaucher disease, ranging from 11% for anti-ribonucleoprotein, anti-pyruvate dehydrogenase and anti-DNA antibodies to 57% for rheumatoid factor [111].…”
Section: Glycosphingolipids and Neuroinflammation: Insights From Lysomentioning
confidence: 99%
“…Also, Zahran and colleagues used three-color flow cytometric immunophenotyping for determination of the frequency of lymphocyte subpopulations and activated T lymphocytes in the peripheral blood among eighteen children with Gaucher disease type 1. They showed increases in the frequencies of activated T lymphocytes (CD3+HLA-DR+ ), activated T-helper cells (CD4+HLA-DR+) and activated T-suppressor/cytotoxic cells (CD8+HLA-DR+) in Gaucher disease type 1 as compared to healthy children [110]. Shoenfeld and coworkers demonstrated a significant increase in the incidence of autoantibodies against 14 autoantigens in the sera of 43 patients with Gaucher disease, ranging from 11% for anti-ribonucleoprotein, anti-pyruvate dehydrogenase and anti-DNA antibodies to 57% for rheumatoid factor [111].…”
Section: Glycosphingolipids and Neuroinflammation: Insights From Lysomentioning
confidence: 99%
“…CD8 + T cells are important for inducing autoimmune and the anti-cancer and anti-viral responses [ 37 , 38 , 39 , 40 ]. T cell defects, T cell lymphomas, and increased incidence of CD3 + , CD4 + , CD8 + , CD3 + HLA-DR + , CD4 + HLA-DR + , and CD8 + HLA-DR + subset of activated T cells have been observed in lung and peripheral blood of patients with GD [ 41 , 42 , 43 , 44 , 45 , 46 ]. Significantly elevated levels of CD4 + T cells and modest changes in CD8 + T cells were present in liver, lung, spleen, and thymus of Gba1 9V/− mice [ 5 , 6 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…IFNγ drives increased expression of CXCR3 and its ligands, (e.g., CXCL9–11) that are increased in several inflammatory diseases [ 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Elevated levels of IFNγ and CXCL9–11 as well as increased numbers of tissue T cells were found in GD mouse models and human patients with GD [ 5 , 6 , 15 , 41 , 42 , 43 , 44 , 45 , 47 , 71 ]. However, the cellular mechanism(s) that causes increased tissue recruitment of T cells in Gba1 9V/− mice is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Gaucher disease (GD) is a lysosomal storage disease caused by the deficiency of glucocerebrosidase enzyme, leading to the accumulation of undigested glucosylceramide in the reticuloendothelial system cells mainly the macrophages (Gaucher cells), which accumulate in different organs mainly bone marrow, spleen, and liver giving the disease its distinct clinical picture. 1 Although less common, the heart, lungs, and kidneys may be infiltrated by Gaucher cells. 2,3 T-lymphocytes perform and regulate many of the immune processes and play a major role in immune homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…It is still not fully known how GD leads to the altered biochemical and immunological cellular functions observed in the disease. [1][2][3] Previous studies have shown a significant reduction in CD4 þ , Tgd2, and natural killer (NK) T-cells and a significant increase in CD4 þ memory cells. While other studies have confirmed decreased numbers of CD4 þ and CD8 þ , others have found an increase in CD8 þ and a decrease in CD4 þ , which was independent of whether patients received enzyme replacement therapy (ERT) or not.…”
Section: Introductionmentioning
confidence: 99%